EVALUASI IMPLEMENTASI PERSYARATAN HALAL PRODUKSI PRODUK TABLET VITAMIN C DI PT. X - Sabiti, Farroh Bintang; Wijaya, Gabriell Angela Monique; Sholeh, Aries Badrus; Rakhmaningsih, Haninta (Cendekia Journal of Pharmacy, 2024)
Indonesia is a country with a Muslim-majority population reaching up to 87.18%. therefore, the government guarantees that citizens consume halal products as stated in UU No. 33 Th. 2014 about the guarantee of halal products as a halal regulation of food products, including pharmaceutical preparation. As a pharmaceutical industry, PT. X evaluates the criteria of halal products. This research evaluated the implementation of the halal production requirement of Vitamin C tablet at PT. X. This observational, practical research and interview method evaluated the data by analyzing and checking the halal requirement components. Evaluation is carried out by analysis using the checklist method. The researchers adjusted the 12 indicators of halal production of Vitamin C tablet at PT. X. Data collection was carried out by filling out a checklist from The Indonesian Council of Ulama (MUI) regarding halal criteria at the production stage of pharmaceutical products at PT. X. Based on the research results, it is known that the production process doesn't fulfill all the indicators for halal production implementation for Vitamin C tablet at PT. X with a percentage of 75%. However, PT. X has made efforts to ensure that the products produced are not contaminated with haram/unclean materials. Therefore, it can be concluded that the vitamin C products from PT. X are guaranteed to be halal.Keywords: Pharmaceutical Industry, Production, Halal